EP300-mediated H3K18la regulation of METTL3 promotes macrophage ferroptosis and atherosclerosis through the m6A modification of SLC7A11 - Chen, Jingquan; Liu, Zongrong; Yue, Zhujun; Tan, Qiang; Yin, Hongshun; Wang, Haifei; Chen, Zhilong; Zhu, Yanbing; Zheng, Jianghua (Biochimica et biophysica acta. General subjects, 2025)
Macrophages, as the primary immune cell population in atherosclerosis (AS), exhibit complex pathogenic mechanisms that are not fully elucidated. This study aims to explore the interplay between histone lactylation and methyltransferase-like protein 3 (METTL3)-mediated m6A modification and their potential mechanisms in AS. We demonstrate that METTL3 is highly expressed in macrophages in both in vivo and in vitro models of atherosclerosis, and myeloid cell-specific deletion of METTL3 attenuates the progression of atherosclerosis. Furthermore, the accumulation of lactate levels in macrophages promotes METTL3 expression through EP300-mediated histone H3 lysine 18 lactylation (H3K18la) binding to the METTL3 promoter site. We found that METTL3-mediated m6A modifications are enriched in solute carrier family 7 member 11 (SLC7A11) and accelerate its mRNA degradation in a YTH domain family member 2 (YTHDF2)-dependent manner, thereby promoting ferroptosis in macrophages. Additionally, lactate stimulation downregulates SLC7A11 through the METTL3/YTHDF2 pathway, further promoting ferroptosis. Overall, during AS, lipid peroxidation induces an increase in lactate levels within macrophages, which enhances METTL3 expression through EP300-mediated H3K18la. This further accelerates the degradation of SLC7A11 mRNA via the YTHDF2-dependent m6A modification pathway, inducing ferroptosis in macrophages. This discovery provides new insights into the mechanisms of macrophage function in AS and offers a theoretical basis for the development of therapies for AS. •In AS, METTL3 expression is elevated in macrophages, and its myeloid-specific deletion slows atherosclerosis progression.•In AS, elevated lactate levels in macrophages promote METTL3 expression by enabling EP300-mediated H3K18la binding to the METTL3 promoter.•METTL3-mediated m6A modifications enrich in SLC7A11 and accelerate its mRNA degradation via YTHDF2, promoting macrophage ferroptosis.